Advancing HE through the voice(s) of experience - Ingham, Deena (ICAReAlumni Conference Proceedings, 2019)
This original mixed methods study identified the potential of a systematically sought and sustained seeking of the Graduate Voice over time to inform academics, institutions and policy makers alike in Higher Education (HE). It was conducted with 202 responding graduates from across the globe who completed degrees at English universities across all institutional mission groups during the 1970s, 80s, 90s and 2000s. The Graduate Voice currently appears selectively in HE through interventions in academic courses as providers of placements, careers talks, informed expert guest lectures, alumni awards, buddy schemes or high-profile alumni philanthropy (Warren et al, 2014). According to the findings of this research study, graduates considered their potential contributions undervalued by their institutions in terms of what they can do for their university (Gallo, 2012) in this important mutual relationship. Graduates identified that many would never achieve roles as financial philanthropists but considered they had significant contributions to offer as informed participants, employers, parents, ambassadors and evaluators. Most had never been asked to constructively reflect on their perceived value of their degrees or to contribute their perspective, something they identified as a missed opportunity. The research indicates significant advantages in maintaining intensive relationships with almae matres and placing the Graduate Voice at the heart of 21st century higher education. Building this key relationship supports individuals, institutions and the sector in providing informed perceptions to influence prospective students, current students, policy markers, alumni networks and institutional advancement. The potential capacity of developing this vital ongoing relationship for individual institutions to sustain their unique offering and identities in an increasingly competitive marketplace was a fature of the research. An additional outcome of the study was the indication of significant individual and sectoral risks if the Graduate Voice should be ignored.